2016
DOI: 10.19128/turje.51242
|View full text |Cite
|
Sign up to set email alerts
|

7th Grade Students’ Mathematical Difficulties in Force and Motion Unit

Abstract: Integration of science and mathematics as well as with other disciplines is overarching goal of science education. In spite of its importance, teachers have concerns about mathematical difficulties that their students encounter during their teaching. One of the most common subjects that students have mathematical difficulties was reported as physics. With this regard, the present study is aimed to investigate seventh grade students' mathematical errors in a physics related subject, specifically force and motio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In the same vein, pre-service physics teachers [4] and science teachers [69] experienced mathematics-based difficulties such as the failure to complete mathematical operations correctly through the teaching sequences. Howe et al [70] as well as Cebesoy and Yeniterzi [71] also found that that the students faced problems regarding mathematics when studying science/physics concepts. Aycan and Yumus ¸ak [1] underlined the importance of mathematics knowledge and skills in the context of grasping physics topics.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 95%
“…In the same vein, pre-service physics teachers [4] and science teachers [69] experienced mathematics-based difficulties such as the failure to complete mathematical operations correctly through the teaching sequences. Howe et al [70] as well as Cebesoy and Yeniterzi [71] also found that that the students faced problems regarding mathematics when studying science/physics concepts. Aycan and Yumus ¸ak [1] underlined the importance of mathematics knowledge and skills in the context of grasping physics topics.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 95%
“…In addition, according to Akatugba and Wallace [6] study, proportional reasoning not only related to the science concept understanding but also related to problem-solving in cultural, social, cognitive, and contextual elements in learning physics. However, many students still difficult to understand ratio and proportion in science concepts [7].…”
Section: Introductionmentioning
confidence: 99%